Clinical study on the efficacy and safety of treatment of both proliferative and membranous lupus nephritis with multi-target therapy - HUANG Jin-ping; YU Yan-zhi; GAO Wu; CHEN Wen; HUA Du-juan; WU Yi-zhe; JIANG Jin-yu (Linchuang shenzangbing zazhi)
Objective To investigate the efficacy and safety of treatment of both proliferative and membranous lupus nephritis with multi-target therapy.Methods Thirty-two patients were randomly divided into multi-target therapy group and cyclophosphamide(CTX) group.The induction course of treatment was initially set to 24 weeks,and it was prolonged to 36 weeks if subjects did not achieve complete remission within 24 weeks.Two groups of patients were treated with intravenous methylprednisolone after oral prednisone therapy.Tacrolimus(TAC) was given at 4 mg/d,and mycopholatemofetil(MMF) 1.0 g/d.CTX was given monthly 0.75 g/m~2 BSA.All enrolled patients were subjected to renal puncture 2 weeks before therapy.Lupus activity index(AI) and chronic index(CI)were estimated by semi-quantitative scores in the renal tissue.After 36 weeks of treatment,serum cytomegalovirus(CMV) antibody was tested.When patients had signs of bacterial infection,B ultrasound,chest CT,and bacterial culture were performed to identify the site and bacterial species of infection according to the clinical needs.Results The complete remission rate in the multi-target therapy group was significantly higher than that in the CTX group after both 24 weeks(62.50%vs.18.75%,P<0.01) and 36 weeks(68.75%vs.31.25%,P<0.05),respectively.Kaplan-Meier analysis showed that subjects in the multi-target group achieved both partial and complete remission earlier than in the CTX group(P<0.01).CMV infection(43.75%) was the major adverse effect of multi-target therapy.Conclusions Multi-target therapy is superior to CTX therapy for both proliferative and membranous lupus nephritis.Although the risk of CMV infection is high,the patient is well tolerated.